INTESTINAL PARASITES IN RESIDENTS OF TWO LOCALITIES OF YURIMAGUAS, ALTO AMAZONAS, LORETO, PERU - Pascual, Gissela (2010)
Intestinal parasites are a health problem in Peru. The aim of this study was to determine the prevalence of intestinal parasites in 66 residents of two towns in Yurimaguas: Farmhouse Grau (Location #1) and four settlements: Buena Vista, La Molina, Natividad and Madeiros (Location #2), Alto Amazonas, Loreto, Peru. An observational, analytical, descriptive cross-sectional and prospective study was performed from February to March 2010. Parasitological analyses were done using the direct method and temporary staining with Lugol. For the differentiation of species of Ancylostoma, Harada-Mori method was used. A total of 10 parasitic protozoa and five helminths were detected. Among the protozoa, the most prevalent were Entamoeba coli (Grassi, 1879) (48.4%) and Giardia lamblia (Lamb, 1859) (16.6%). The most prevalent helminths were Ascaris lumbricoides Linnaeus, 1758 (43.8%) and Trichuris trichiura (Linnaeus, 1771) (19.7%). The most prevalent infected age group was 4-7 years (94.1%). 24.3% were negative for enteroparasites, 22.7% had one parasite, 25.7% had two parasites, and 22.7% and 4.6% had three and four parasites, respectively. The three samples positive to Uncinarias were identificated as Necator americanus (Dubini 1843). Trichuris trichiura was more prevalent at location #2. The enteric protozoans were more prevalent than helminths. Finally, co-infection between E. coli, G. lamblia, and between A. lumbricoides, T. trichiura were observed.